2022
DOI: 10.1155/2022/5474397
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tobacco Use on COVID-19 Outcomes: A Systematic Review

Abstract: Introduction. Tobacco use increases risks for numerous diseases, including respiratory illnesses. We examined the literature to determine whether a history of tobacco use increases risks for adverse outcomes among COVID-19 patients. Methods. We conducted a systematic search of PubMed, LitCovid, Scopus, and Europe PMC (for preprints) using COVID-19 and tobacco-related terms. We included studies of human subjects with lab-confirmed COVID-19 infections that examined tobacco use history as an exposure and used mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
0
25
0
1
Order By: Relevance
“…A convincing association between unhealthy lifestyle behaviors and poorer outcomes associated with COVID-19 infection (e.g., hospitalization and mortality risk) has already been demonstrated and communicated by the CDC in public health messaging. 2 , 3 , 4 , 5 , 6 , 7 These behaviors and conditions included physical activity, obesity, diabetes, and smoking. Sallis et al 8 reported that individuals infected with COVID-19 were at significantly higher risk for hospitalization if they reported a sedentary lifestyle prior to diagnosis.…”
mentioning
confidence: 99%
“…A convincing association between unhealthy lifestyle behaviors and poorer outcomes associated with COVID-19 infection (e.g., hospitalization and mortality risk) has already been demonstrated and communicated by the CDC in public health messaging. 2 , 3 , 4 , 5 , 6 , 7 These behaviors and conditions included physical activity, obesity, diabetes, and smoking. Sallis et al 8 reported that individuals infected with COVID-19 were at significantly higher risk for hospitalization if they reported a sedentary lifestyle prior to diagnosis.…”
mentioning
confidence: 99%
“…This study underscores the impact of COVID-19 on young adults’ e-cigarette use, particularly via changes in accessibility to vaping products due to retail disruptions and state-order business closures, stress, boredom, and changes in the daily environment. Quantitative findings suggested that roughly one-fifth of participants made attempts to cut down or quit vaping (respectively), and some interview participants reported decreasing their use, reflecting literature indicating a decrease in the use of current e-cigarette use among young adults 5 , 7 , 8 , 12 .…”
Section: Discussionmentioning
confidence: 88%
“…Several factors may have driven decreases in e-cigarette use, or increased attempts to cut down or quit. For example, about a quarter of participants reported living at home with parents or guardians, which is associated with less e-cigarette use 5 , 7 , 8 , 12 . Additionally, others worried about the impact of vaping on their lung function, particularly during COVID-19, and some experienced disruptions in e-cigarette supply and demand 5 , 7 , 8 , 12 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, una limitación del estudio fue no considerar otro tipo de sustancias además de la nicotina, y tampoco los cigarros electrónicos. (Archie SR, et al, 2020;Baker J, et al, 2022) La hipertensión arterial y la diabetes mellitus, son factores de riesgo cardiovascular; y su asociación al evento cerebrovascular está ampliamente demostrado en estudios. Sin embargo, al relacionarlo con COVID-19 aún quedan dudas si el antecedente de la infección, por si solo desencadena el evento cerebrovascular o si la hipertensión y diabetes, como ya comentado, los factores de riesgo cardiovascular desencadenantes.…”
Section: Discussionunclassified